Risks of dengue secondary infective biting associated with aedes aegypti in home environments in Monterrey, Mexico - Ramírez Jiménez, Rocío; Zárate Nahón, Erwy Arvid; Alvarado Moreno, Marcela Selene; Sánchez Casas, Rosa María; Laguna Aguilar, Maricela; Sánchez Rodríguez, Olga Saraí; Torres Zapata, Raúl; Rivas Estilla, Ana María; Ramos Jiménez, Javier; Medina de la Garza, Carlos Eduardo; Zacarías Villareas, Jesús; Ibarra Juárez, Luis Arturo; et al. (Southwestern Entomologist, 2013)
Abstract. Secondary dengue virus infections are a major risk for developing dengue hemorrhagic fever. Recent exposure to infectious bites of Aedes aegypti (L.) females in previously diagnosed dengue cases fulfills the epidemiological model of dengue hemorrhagic fever. A study was comprised of 357 (89.2%) dengue and 43 (10.8%) dengue hemorrhagic fever cases confirmed by laboratory tests and clinical manifestations. An entomological survey was done in homes and backyards. Concurrently, a questionnaire was used to assess the impact of healthpromotion campaigns through knowledge of the vector and its epidemiological role. Seventy-six (28.4%) of the 268 (67.0%) total wet or dry oviposition sites were positive for the presence of larvae or pupae, while adult Ae. aegypti were found in 32 (8.0%). One hundred thirty-two (33%) householders who formerly had dengue fever or dengue hemorrhagic fever had knowledge of either larval or adult dengue vector stages. According to gender distribution, 145 (36.2%) and 14 (3.5%) of the males confirmed with cases of dengue and dengue hemorrhagic fever lived in houses with 17.9 and 2% of the Ae. aegypti larval and pupal habitats. Houses with females who had dengue and dengue hemorrhagic fever were 212 (53%) and 29 (7.3%), with containers with immature Ae. aegypti in 19.4 and 7%, respectively. Lack of sustainability of government-targeted health education campaigns is the major problem for involving communities in prevention and control of dengue